Character Profile of Caring and Responsibility of Inclusive Learners in Senior High School - Wulandari, Eka Mia; Yani, Muhammad Turhan; Jatiningsih, Oksiana (International Journal of Emerging Research and Review, 2025)
Objective: This study was conducted to analyze the profile of caring and responsible characters of inclusive students in high school. The main focus of this study is to analyze the caring and responsible characters possessed by inclusive students at the high school level. Based on this focus, the formulation of the problem in this study is how the profile of caring and responsible characters of inclusive students in high school. The substance of this study focuses on describing the caring and responsible characters of inclusive students and the factors that influence the caring and responsible characters of inclusive students. Method: The research method used is descriptive and does not conduct hypothesis testing with a sample of 3 teachers, namely 1 GPK teacher, 1 BK teacher, 1 subject teacher, 1 non-inclusive student, and 2 inclusive students. The sampling technique used purposive sampling, where each sample was taken from a representative level of inclusive participants. Data collection was carried out at Public Senior High School 1 (SMAN 1) Gedangan, East Java. Data collection techniques used questionnaires, interviews, and observations whose data results would be analyzed descriptively qualitatively. Results: The results of the data obtained were analyzed using qualitative descriptive analysis techniques. The results of the study indicate that 1) the caring and responsible character of inclusive students is low and because the social character of inclusive students is also low. 2) Students' self-confidence is low because they feel alone at school and do not have friends who understand them. 3) Some teachers sometimes pay less attention to inclusive students when teaching and focus more on regular students. 4) Regular friends in class sometimes still underestimate and do not embrace inclusive friends. Novelty: What is new in this study is the focus on inclusive students at the high school level, integrating the analysis of two main characters, namely caring and responsibility, in one comprehensive study, and considering the specific context of inclusive schools at the high school level and providing insight into how caring and responsible characters develop in diverse environments. This is important because the dynamics and challenges in inclusive schools are different from regular schools.